2022
DOI: 10.1371/journal.pone.0264548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of the artemisinin resistance Kelch 13 gene in Plasmodium falciparum from Nigeria

Abstract: Accurate assessment and monitoring of the Plasmodium falciparum Kelch 13 (pfk13) gene associated with artemisinin resistance is critical to understand the emergence and spread of drug-resistant parasites in malaria-endemic regions. In this study, we evaluated the genomic profile of the pfk13 gene associated with artemisinin resistance in P. falciparum in Nigerian children by targeted sequencing of the pfk13 gene. Genomic DNA was extracted from 332 dried blood (DBS) spot filter paper samples from three Nigerian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
(51 reference statements)
2
7
0
Order By: Relevance
“…The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [31]. C469C, a common synonymous mutant allele of pfK13 found in African isolates, the proportion in our study was similar as that in Burkina Faso and Senegal [32][33][34]. The pfK13 mutation allele S549S, to our knowledge, was rstly identi ed in the migrant workers from Guinea, Equatorial Guinea, and The Democratic Republic of the Congo (Congo DRC).…”
Section: Discussionsupporting
confidence: 88%
“…The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [31]. C469C, a common synonymous mutant allele of pfK13 found in African isolates, the proportion in our study was similar as that in Burkina Faso and Senegal [32][33][34]. The pfK13 mutation allele S549S, to our knowledge, was rstly identi ed in the migrant workers from Guinea, Equatorial Guinea, and The Democratic Republic of the Congo (Congo DRC).…”
Section: Discussionsupporting
confidence: 88%
“…The all 3 Q613H were detected in the migrant workers from Nigeria, which was similar as reported before [ 34 ]. The synonymous mutant allele C469C, which was common in Africa, was identified in this study and the proportion was similar as reported in Burkina Faso and Senegal [ 35 37 ]. The Pfk13 mutant allele S549S, to our knowledge, was firstly identified in the migrant workers from Guinea, Equatorial Guinea, and Congo DRC.…”
Section: Discussionsupporting
confidence: 88%
“…No mutations in kelch13 were identified that have previously been associated with artemisinin resistance. Five kelch13 mutations were identified, three synonymous changes (A627A and S649S (both in Navrongo), and a sample from Accra with C469C), and two non-synonymous mutations: Q613H (in Accra) and N629Y (in Navrongo), which have previously been reported in West Africa [78,79] and are not considered to be associated with artemisinin resistance ( Supplementary Notes ).…”
Section: Resultsmentioning
confidence: 98%
“…Q613H (in Accra) and N629Y (in Navrongo), which have previously been reported in West Africa [78,79] and are not considered to be associated with artemisinin resistance (Supplementary Notes).…”
Section: Drug Resistance Marker Frequenciesmentioning
confidence: 84%